(untitled) (Praxis Educativa, 2023)
This article shares the uncertainties, curiosities and disciplinary promiscuities from which the methodolo(R)gy of the doctoral research that I am carrying out about the visualities and sensitive experiences of the menstrual cycle in secondary schools is developed. The narrative and (auto)biographical approach with a situated and queer feminist positioning, in resonance with the visual rhetoric, the gazes and the performance sheltered from Art as a vital language configures the (aesthetic) political proposal that is shared here and from the which this thesis is built. At the same time, this proposal seeks to be a contribution to the demarcation of the understanding of colonial modern science with an objective, empirical and universal claim.